تطوير نموذج العلوم الاسلامية فى التعليم العالي الإسلامي بإندونيسيا (دراسة نقدية فى جامعة أمبون الاسلامية الحكومية) - Karman Karman (Jurnal Pendidikan Islam, 2016)
This study explains the development paradigm of Islamic studies in the College (PTAI) that is inspired by the transformation of science that has developed along with the demands of a globalized world which is marked the transformation of information technology or information civilization. This study is a library research at IAIN Ambon. The research resource includes the book of the Scientific Development Paradigm at IAIN Ambon with hermeneutic and deconstructive approach and critical analysis. Based on the research concluded: (1) Scientific paradigm developed in Ambon IAIN is interconnected-integrated paradigm in the metaphor of bees, where all sciences are closely related each other; and (2) the development of integrated-interconnected paradigm at Ambon IAIN conceptually is not fully relevant to the idea of founding fathers on this paradigm. It seems immature and not yet supported by the strong philosophy principles.